2016
DOI: 10.1177/1073191115591595
|View full text |Cite
|
Sign up to set email alerts
|

Item Response Theory Analysis of ADHD Symptoms in Children With and Without ADHD

Abstract: Item response theory (IRT) was separately applied to parent- and teacher-rated symptoms of attention-deficit/hyperactivity disorder (ADHD) from a pooled sample of 526 six- to twelve-year-old children with and without ADHD. The dimensional structure ADHD was first examined using confirmatory factor analyses, including the bifactor model. A general ADHD factor and two group factors, representing inattentive and hyperactive/impulsive dimensions, optimally fit the data. Using the graded response model, we estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 59 publications
5
28
1
1
Order By: Relevance
“…Nevertheless, the prevalence of inattentive type presentation in our sample was comparable with meta-analytic findings (Willcutt, 2012). This could be partially explained by findings from Li et al (2015), who evaluated the full scale and found that two of the items missing from our scale had significant local dependence (di5 and di7; Li et al, 2015). Also, Arias et al (2018) analyzed the full scale and found that the most information was provided by three items (dh5, di2, and di8; relative weakness of dh6, we did not consider this an aberration, because other studies using typical levels of scale measurement also found dh6 to be a weaker item in terms of information provided (Arias et al, 2018;Gomez, 2011;Li et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Nevertheless, the prevalence of inattentive type presentation in our sample was comparable with meta-analytic findings (Willcutt, 2012). This could be partially explained by findings from Li et al (2015), who evaluated the full scale and found that two of the items missing from our scale had significant local dependence (di5 and di7; Li et al, 2015). Also, Arias et al (2018) analyzed the full scale and found that the most information was provided by three items (dh5, di2, and di8; relative weakness of dh6, we did not consider this an aberration, because other studies using typical levels of scale measurement also found dh6 to be a weaker item in terms of information provided (Arias et al, 2018;Gomez, 2011;Li et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…We accepted the high difficulty because it provides information at higher levels of the trait, which is desirable for our purposes. Regarding the relative weakness of dh6, we did not consider this an aberration, because other studies using typical levels of scale measurement also found dh6 to be a weaker item in terms of information provided (Arias et al, ; Gomez, ; Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations